Kontekstualisasi Kebijakan Fiskal Zakat dalam Mengentaskan Kemiskinan di Indonesia (Studi Kebijakan Umar bin Khattab) - Izza, Rihadatul Izza (ITB AAS INDONESIA Surakarta, 2024)
Indonesia is one of the developing countries in the world which has quite high cases of poverty, namely 9.36% of the total population of Indonesia. Poverty in the Islamic framework is seen as a lack of access to fulfilling primary needs, for example food and shelter. Therefore, massive efforts are needed to overcome the problem of poverty. Islam has the main goal of achieving the welfare of humanity, which is assisted by state financial policies in accordance with Islamic principles. Islamic state financial policy to overcome poverty is one of them through the instrument of zakat. The zakat management system during the time of Caliph Umar bin Khattab experienced rapid development, this was demonstrated by the formation of the Baitul Mal institution which specifically handled state finances with the main aim of improving the welfare of Muslims. This research uses descriptive qualitative research to examine the contextualization of zakat fiscal policy in an effort to eradicate the problem of poverty in Indonesia which refers to the public financial system, especially fiscal policy through the Baitul Maal institution during the reign of Umar bin Khattab's caliphate.